Comparative proteomic analysis of serum from nonhuman primates administered BIO 300: a promising radiation countermeasure - Girgis, Michael (Sci Rep, 2020)
Hematopoietic acute radiation syndrome (H-ARS) and delayed effects of acute radiation exposure (DEARE) are detrimental health effects that occur after exposure to high doses of ionizing radiation. BIO 300, a synthetic genistein nanosuspension, was previously proven safe and effective against H-ARS when administered (via the oral (po) or intramuscular (im) route) prior to exposure to lethal doses of total-body radiation. In this study, we evaluated the proteomic changes in serum of nonhuman primates (NHP) after administering BIO 300 by different routes (po and im). We utilized nanoflow-ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (NanoUPLC-MS/MS) methods for comprehensive global profiling and quantification of serum proteins. The results corroborate previous findings that suggest a very similar metabolic profile following both routes of drug administration. Furthermore, we observed minor alterations in protein levels, 2 hours after drug administration, which relates to the C(max) of BIO 300 for both routes of administration. Taken together, this assessment may provide an insight into the mechanism of radioprotection of BIO 300 and a reasonable illustration of the pharmacodynamics of this radiation countermeasure.